2008
DOI: 10.1159/000119707
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Twenty Lysine-Peptoid Hybrids against Clinically Relevant Bacteria and Fungi

Abstract: Background: This paper describes the antimicrobial activities of 20 lysine-peptoid hybrids against a selection of clinically relevant bacteria and fungi. Methods: Minimal inhibitory concentrations were determined against methicillin-susceptible Staphylococcus aureus (ATCC 29213), methicillin-resistant S. aureus (ATCC 33591), vancomycin-intermediate S. aureus (ATCC 700699 MU50), vancomycin-resistant Enterococcus faecium (ATCC 700221), Pseudomonas aeruginosa (ATCC 27853), Salmonella typhimurium (clinical isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 32 publications
2
55
0
Order By: Relevance
“…To reflect the clinical scenario more closely, the impact of systemic infection with P. aeruginosa on the brain uptake of colistin was assessed in a mouse model. The strain of P. aeruginosa selected to induce bacteremia (ATCC 27853) was initially isolated from a patient and has been widely used to determine the antimicrobial activities of various antibiotics (15,35), and therefore, it was considered clinically relevant for this study. It has been shown that inoculation of mice with Escherichia coli and Streptococcus pneumoniae at sepsis-inducing doses leads to BBB disruption, which was demonstrated by brain access of the impermeable horseradish peroxidase (38).…”
Section: Discussionmentioning
confidence: 99%
“…To reflect the clinical scenario more closely, the impact of systemic infection with P. aeruginosa on the brain uptake of colistin was assessed in a mouse model. The strain of P. aeruginosa selected to induce bacteremia (ATCC 27853) was initially isolated from a patient and has been widely used to determine the antimicrobial activities of various antibiotics (15,35), and therefore, it was considered clinically relevant for this study. It has been shown that inoculation of mice with Escherichia coli and Streptococcus pneumoniae at sepsis-inducing doses leads to BBB disruption, which was demonstrated by brain access of the impermeable horseradish peroxidase (38).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic antimicrobial peptidomimetics (SAMPs) are a new class of drugs with activity against Gram-positive and Gram-negative bacterial species (14). LTX-109 (Lytixar; Lytix Biopharma AS, Oslo, Norway) is one such novel SAMP which rapidly kills bacteria via membrane disruption and has not been associated with cross-resistance to other available drugs.…”
mentioning
confidence: 99%
“…The names, sequences, hydrophobicities, antibacterial activities against Gram-negative (E. coli) and Gram-positive (B. subtilis) bacteria, and hemolytic activities of these nine compounds are shown in Table 1 (values in g/ml are provided in Table S1 in the supplemental material). The antibacterial activities are reported as MICs and were determined according to standard CLSI M7-A6 protocols (6); hemolytic activities, determined as previously reported (5), serve as a measure of antimicrobial peptide/peptoid toxicity (9), which is commonly used to optimize antimicrobial peptide/peptoid therapeutic performance (4,5,17,19,(22)(23)(24).…”
mentioning
confidence: 99%